The Routledge Companion to History and the Moving Image (Taylor & Francis, 2024)
The Routledge Companion to History and the Moving Image takes an interdisciplinary approach to understanding history in moving images. It engages this popular and dynamic field that has evolved rapidly from film and television to digital streaming into the age of user-created content. The volume addresses moving image history through a theoretical lens; modes and genres; representation, race, and identity; and evolving forms and formats. It brings together a range of scholars from across the globe who specialize in film and media studies, cultural studies, history, philosophy of history, and education. Together, the chapters provide a necessary contemporary analysis that covers new developments and questions that arise from the shift to digital screen culture. The book examines technological and ethical concerns stemming from today's media landscape, but it also considers the artificial construction of the boundaries between professional expertise and amateur production. Each contributor?s unique approach highlights the necessity of engaging with moving images for the academic discipline of history. The collection, written for a global audience, offers accessible discussions of historiography and a compelling resource for advanced undergraduates and postgraduates in history, film and media studies, and communications.